The Philosophy of Perennialism - Pratiwi, Dinny Hariyati (Yayasan Sembilan Pemuda Indonesia, 2023)
Perennialism is a teacher-centered educational philosophy that focuses on timeless ideas and universal truths. Apart from that, the educational philosophy of perennialism means growing with time and being eternal. The view of this philosophy is to believe that the values and morals that develop in society are eternal. The role of this philosophy is to realize the abilities possessed by students as one of the basic potentials. Truth in this school is universal and constant. Educational objectives are material-centered (content-based, subject-centered), one of which is in the discipline of history. Perennialism suggests that the focus of education should be ideas that have survived through the centuries, believing that these ideas are as relevant and meaningful today as when they were written. This Educational Philosophy aims to prepare students for life by developing their intellectual and moral qualities through an emphasis on knowledge and the meaning of knowledge, serving to improve students’ critical thinking skills in their search for individual freedom, human rights and responsibility through nature.